From Issues to Actions: The Importance of Individual Concerns and Organizational Values in Responding to Natural Environmental Issues - Bansal, Pratima (Organization Science, 2003)
In this research, we traced the development of natural environmental issues in two organizations in real time over the period of a year. Participant observations, discussions with organizational members, and corporate documents yielded insights used to develop a model describing issue flows in both organizations. With this model, we identified the factors that influenced the scope, scale, and speed of organizational response to issues. Our methods provided insights into why issues generated organizational responses and also why they did not. Two factors appeared to be critical in explaining organizational responses to issues: individual concerns and organizational values. Individual concerns gave rise to an issue champion or seller. An issue consistent with organizational values was perceived as strategic. These were necessary conditions; without either condition, the issue would not be resolved. It is argued further that individual discretion and excess resource slack will moderate the relationship between these direct effects and the scope, scale, and speed of organizational response. The framework that emerged from the data is conveyed through a set of four propositions.